Considerações para o controle tecnológico de obras em alvenaria estrutural - Canato, Ricardo Luiz (Universidade Federal de São Carlos, 2015)
Masonry is known as a building structure for thousands of years. Cases where masonry elements (several units laided together bonded or not with mortar and grouting) support the building structure are widely found. Until mid-19th century, almost all structures had masonry part of its structural elements, although not all historic construction can be called structural masonry the way we understand it today with high strength blocks. The great expansion on the use of structural masonry occurred after the development of specific techniques and equipment. Moreover, technological development has enabled the production of higher strength blocks, dimensional precision and uniformity. To certify the design specified quality, there is the need of construction technologic control. This is the guarantee of minimum structural performance. Quality control is necessary to receive (or acceptance) the materials and components, including blocks, concrete, grout and the mortar, and finally the acceptance of masonry. This paper presents an assessment of the masonry quality control. Two parts has focus in different topics. In the first, field study cases in São Carlos city are assessed. The cases include concrete and ceramic blocks masonry building, and the quality control plan of each case were checked. The other part, focus on evaluating the several quality control tests on prisms compressive strength. From an extensive database, simulations concerning on the calculation of the characteristic value and coefficients of variation of samples, are assessed and weighted. As a conclusion, we can point that the quality control as required by Brazilian standards are not always followed in practice. About the prism test, we suggest considering to evaluate standard sample size specified today. It may be possible to reduce the number of specimens in each sample.
Keywords: Alvenaria estrutural; Controle de obras; Ensaios; Construção civil; Structural masonry; Quality control works; Testing; Civil construction; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS